Socio-demographic correlation to zakat participation during the Covid-19 pandemic in Indonesia - Napitupulu, Rodame Monitorir (Indonesian Journal of Islamic Economics Research, 2023)
The Covid-19 pandemic that has occurred in various countries including Indonesia is a concern for various parties. It seems that it is starting to be felt in various professional backgrounds including in the economy. One of the Islamic financial instruments that can help improve current economic conditions is zakat. This study aims to determine various socio-demographic variables (zone, domicile, age, gender, occupation, latest education, income per month, average expenditure per month). This research was conducted with a descriptive quantitative approach with a total sample size of 396 people with techniques and data through an electronic questionnaire within a period of 1 month. Further data were analyzed by cross tabulation and correlation Pearson (r value). Based on the results of the study, it is known that there are 3 variables, namely: domicile, occupation, and income per month with the frequency of giving zakat during the Covid-19 pandemic.